Aksara Mandailing sebagai Motif Batik pada Kemeja - Harahap, Mai Yusnanda; Yanuarmi, Dini; Prastawa, Wisnu (Corak, 2024)
AbstractMandailing script is one of the cultural heritage relics of the Mandailing people handed down by ancestors in the form of ancient writing. Mandailing scriptas an idea of creation on batik shirts is a work to raise the local value of the Mandailing people’s wisdom. The concept of creating this work departs from the Mandailing script as a motif on batik shirts. The script that’s applied to the shirt inthe form of the introduction of the induk surat (ina ni surat) and anak surat of the will then be arranged vertically, horizontally and zigzag vertically as sentences in the form of advice in Mandailing. The theoretical basics used in realizing work is form, function, motive, color and aesthetics. The method of creation includes the stages of exploration, design and materialization. The materials used are mori primissima and remasol dyes. The techniques used in the creation of works are batiktulis and sewing. The result of this work is a longsleeved shirt that can be used at formal events such as weddings, meetings and other events. There were 3 shirts works and named, they are "Poda na Lima", " Martanggung Jawab ", and "Hatoguan"AbstrakAksara Mandailing merupakan salah satu peninggalan warisan budaya masyarakat Mandailing yang diturunkan oleh nenek moyang berupa tulisan kuno. Aksara Mandailing sebagai ide penciptaan pada kemeja batik merupakan sebuah usaha untuk mengangkat nilai kearifan lokal masyarakat Mandailing. Konsep penciptaan karya ini berangkat dari aksara Mandailing sebagai motif pada kemeja batik. Tulisan aksara diterapkan pada kemeja berupa pengenalan induk surat (ina ni surat) dan anak surat kemudian disusun secara vertikal, horizontal dan zig-zag vertikal berupa kalimat petatah-petitih berupa nasihat yang ada di Mandailing. Landasan teori yang digunakan dalam mewujudkan karya yaitu bentuk, fungsi, motif, warna dan estetis. Metode penciptaan meliputi tahap eksplorasi, perancangan dan perwujudan. Bahan yang digunakan adalah mori primissima dan pewarna remazol. Teknik yang digunakan pada penciptaan karya yaitu batik tulis dan jahit. Bentuk karya berupa kemeja berlengan panjang yang dapat digunakan pada acara formal. Karya yang diciptakan yaitu 3 kemeja dengan judul “Poda na Lima”, “Martanggung Jawab”, dan “Hatoguan”.